A GC-MS-based metabolomics investigation on scallop (Chlamys farreri) during semi-anhydrous living-preservation. (October 2015) - Chen, Shanqiao; Zhang, Chunhua; Xiong, Yuefeng; Tian, Xiaoqing; Liu, Chengchu; Jeevithan, Elango; Wu, Wenhui
Abstract: We investigated the physiological changes in scallops ( Chlamys farreri ) during semi-anhydrous living-preservation using metabolomics method to obtain a guiding theory in optimizing the preservation conditions. Glycogen, lactic acid, and crude protein levels were measured in 1-day intervals for 6 days, the median lethal time. The metabolite profiling of scallops after the preservation duration of 10% lethal time (3 days) was achieved based on methyl chloroformate derivation before GC-MS analysis. Carboxyl acids related to respiration (malic, fumaric, and succinic acids), fatty acids (C18:0, C16:0, and C22:6), and amino acids (phenylalanine, glutamic acid, aspartic acid, isoleucine, glycine, pyroglutamic acid, proline, leucine, and 2-aminoadipic acid) were identified as biomarkers. Our results demonstrated that scallops performed an elevated anaerobiosis and depressed aerobiosis, which were not caused by oxygen insufficiency. The switching of energy metabolism patterns and disorder of the osmotic regulation system were also observed, suggesting that oxygen supply is less important for optimizing semi-anhydrous living-preservation. Industrial relevance: In China, live aquatic products are far more appreciated by consumers than frozen ones. For example, live scallops are more than ten times as expensive as frozen ones in non-local restaurants. However, there is little profit in providing live scallops instead of frozen scallops, due to the high cost of preservation and transportation. Besides the mortality loss, the high costs of running and building the life-preserving condition are the main costs. Thus, optimizing the preservation conditions can reduce the cost. In our case, we introduced metabolomics instead of non-targeted parameter selecting such as the orthogonal test. Based on the elucidated metabolic pathway, we found that oxygen supplementation is not critical. The high cost of building and running oxygen-supplying module in semi-anhydrous living-preservation can be eliminated. Highlights: Temporarily elevation of lactic acid levels was observed by a time series assay. Fifteen biomarkers were screened in scallops by metabolite profiling and pattern recognition. The aerobic respiration of scallops was depressed; this was not caused by hypoxia. The osmotic regulation system, antioxidant system, and neurological processes of scallops were altered during the semi-anhydrous living-preservation.